Long‐Term Implantable, Flexible, and Transparent Neural Interface Based on Ag/Au Core–Shell Nanowires. Issue 10 (4th April 2019) - Araki, Teppei; Yoshida, Fumiaki; Uemura, Takafumi; Noda, Yuki; Yoshimoto, Shusuke; Kaiju, Taro; Suzuki, Takafumi; Hamanaka, Hiroki; Baba, Kousuke; Hayakawa, Hideki; Yabumoto, Taiki; Mochizuki, Hideki; et al.
Abstract: Neural interfaces enabling light transmittance rely on optogenetics to control and monitor specific neural activity, thereby facilitating deeper understanding of intractable diseases. This study reports the material strategy underlying an optogenetic neural interface comprising stretchable and transparent conductive tracks and capable of demonstrating high biocompatibility after long‐term (5‐month) implantation. Ag/Au core–shell nanowires contribute toward improving track performance in terms of stretchability (<60% strain), transparency (<83%), and electrical resistance (15 Ω sq −1 ). The neural interface integrated with gel‐coated exterior microelectrodes preserves low impedance (1.1–3.2 Ω cm 2 ) in a saline solution over the evaluated 5‐month period. Besides the use of efficient conductive materials, surface treatment using antithrombogenic polymer tends to prevent the growth of granulation tissue, thereby facilitating clear monitoring of electrocorticograms (ECoG) in a rodent during chronic implantation. The flexible and transparent neural interface pathologically exhibits noncytotoxicity and low inflammatory response while efficiently recording evoked ECoG in a nonhuman primate via optogenetic stimulation. The proposed highly reliable interface can be employed in multifaceted approaches for translational research based on chronic implants. Abstract : The material strategy concerning a long‐term implantable, stretchable, and transparent neural interface employing a Ag/Au core–shell nanowire is reported. The neural interface is suitably used to monitor electrocorticogram signals, as demonstrated on a rat during implantations of up to 2 months. Performing simultaneous monitoring of and optogenetics on a marmoset with low noise level has also been realized.